Optimalisasi Akses Literasi Produk Hukum Secara Digital di Era Ketebukaan Informasi Publik - Alan Bayu Aji; Marlia Hafny Afrilies; Hesti Ayu Wahyuni; Maya Ruhtiani; Litya Surisdani Anggraeniko (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
The current era of Public Information Openness has had an impact on all sectors of people's lives, one of which is in the field of law. Disclosure of public information is a right of the community and an obligation for the state, in this case the provision of public information in the field of law in the form of legal products. The community is still very low in understanding regarding access to legal product literacy. This can be seen from the fact that there are still many misunderstandings about a draft legal product made by the Government and the DPR. To overcome these problems, through collaboration with the Legal Research and Writing Community, an activity has been carried out on the socialization of legal information documentation literacy. The activity was carried out directly and attended by students with legal backgrounds from several universities in Purwokerto. In carrying out these activities it aims to provide an understanding of how to optimally access legal product literacy digitally. This is considered important because apart from being a source of student knowledge, it can also be a means of effective outreach to the community, so as to minimize misunderstanding of a legal product made by the state.